Characterization of carabao mango (Mangifera indica) kernel derived edible film. - Erada, Rhona Delle
Food processing industries produce a significantly high amount of waste and the most of the percentage is taken up by fruits and vegetables. Mango is the third most important crop in the Philippines and 15-20% of the mango processing waste consists of mango kernel. Three formulations of mango kernel powder and glycerine, 95:5 (MKF95), 85:15 (MKF85) and 75:25 (MKF75) was used in this study to development edible films and were characterized based on water vapour permeability, textual properties and properties. The water vapour permeability (WVP) of the films ranged from 7.97 to 8.61 x 10-10 g m/Pasm2 with MKF75 having the highest permeability and MKF95 the lowest. The hardness of the films ranged from 60-63 g of load with MKF95 having the highest value for hardness and MKF75 the lowest. Elongation at break ranged from 2.61-7.72 mm with MKF75 having the longest elongation while MKF95 had the shortest elongation. Physicochemical properties were expressed in terms of water activity, moisture content, pH and thickness. The aw range of the films are from 0.65-0.67 with MKF95 having the lowest aw value and MKF75 the highest. The films have a moisture content ranging from 9.66-15.24% (w.b.) The pH of the films ranged from 4.91-4.72 with MKF75 as the most acidic and MKF95 the least acidic. The thickness of the different formulations ranged from to 0.1615-0.1320 mm with MKF95 as the highest while MKF75 the thinnest. All three formulations had the thicknesses lower than 0.25 mm therefore are classified as films. Only the hardness of the films was not significantly different while the rest of the properties were significantly different. Film formulation MKF95 has properties of a packaging material are similar to those of sugar packets due to its low WVP and high value for hardness and thickness while the MKF75 film formulation has similar properties to that of cling wrap due to increased elongation and low thickness.